2021
DOI: 10.1186/s13068-021-01986-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective delignification of poplar wood with a newly isolated white-rot basidiomycete Peniophora incarnata T-7 by submerged fermentation to enhance saccharification

Abstract: Background Pretreatment is a critical step required for efficient conversion of woody biomass into biofuels and platform chemicals. Fungal pretreatment is regarded as one of the most promising technology for woody biomass conversion but remains challenging for industrial application. The exploration of potential fungus strain with high efficient delignification and less processing time for woody biomass pretreatment will be valuable for development of biorefinery industry. Here, a newly isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Moreover, on all media, P. lycii LE-BIN 2142 predominantly secreted an FAD-binding domain-containing protein provisionally assigned to the AA7 CAZyme family. In accordance with our data, Ma et al [ 17 ] previously showed that P. incarnata T-7, cultivated in the presence of poplar wood, and Peniophora sp. CBMAI 1063 [ 16 ], cultivated in a bioreactor on a nutritionally reach medium supplemented with CuSO 4 , did not secrete ligninolytic type II peroxidases.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, on all media, P. lycii LE-BIN 2142 predominantly secreted an FAD-binding domain-containing protein provisionally assigned to the AA7 CAZyme family. In accordance with our data, Ma et al [ 17 ] previously showed that P. incarnata T-7, cultivated in the presence of poplar wood, and Peniophora sp. CBMAI 1063 [ 16 ], cultivated in a bioreactor on a nutritionally reach medium supplemented with CuSO 4 , did not secrete ligninolytic type II peroxidases.…”
Section: Discussionsupporting
confidence: 93%
“…CBMAI 1063 cultivated in a bioreactor on a nutritionally rich medium supplemented with CuSO 4 , although cellulases of GH3 and 5 CAZyme families were detected, their relative abundances (measured as spectral count) were significantly lower than that of LPMO and GMC oxidoreductases [ 16 ]. Similarly, while LPMO and GMC oxidoreductases were detected in the exoproteome of Peniophora incarnata T-7 grown in poplar wood-containing media, typical cellulases such as endoglucanases and exoglucanases were absent [ 17 ]. Regarding hemicellulases, the exoproteome of Peniophora sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al. [ 40 ] reported a newly isolated white-rot basidiomycete Peniophora incarnate T-7 that could be employed for poplar wood pretreatment. Significant groups of lignin-degrading enzymes, including laccase, multicopper oxidase, peroxidase and other auxiliary enzymes, were identified in proteins secreted by the strain.…”
Section: Biological Pretreatmentmentioning
confidence: 99%